Analisis Pengendalian Persediaan Bahan Baku Untuk Mengoptimalkan Pengelolaan Tandan Buah Segar (Tbs) Menggunakan Metode Economic Order Quantity (Eoq) Pada Ptpn Iv Pks Tanjung Seumantoh - Ryan Pramanda; Nurmalawati; Dewiyana; Julpan Afandi Panjaitan (Universitas Katolik Darma Cendika, 2024)
This study aims to optimize the amount of raw material inventory at PTPN IV Regional 6 PKS Tanjung Seumantoh using the Economic Order Quantity (EOQ) method. Based on raw material inventory data during the period January-October 2024, it is known that the initial raw material inventory of 667 tons is far from optimal. Through analysis using the EOQ method, it was found that the optimal amount of raw material inventory is 903 tons. The implementation of this method is expected to increase the efficiency of raw material inventory management by reducing the risk of shortages or excess stock, as well as reducing related operational costs. Thus, the company can improve operational performance and the sustainability of its production process.